Limitations of augmentation index in the assessment of wave reflection in normotensive healthy individuals - Hughes,AD; Park,C; Davies,J; Francis,D; Thom,SAM; Mayet,J; Parker,KH (PLOS One, 2013)
ObjectivesAugmentation index (AIx) is widely used as a measure of wave reflection. We compared the relationship between AIx and age, height and sex with ‘gold standard’ measures of wave reflection derived from measurements of pressure and flow to establish how well AIx measures wave reflection.Materials and MethodsMeasurements of carotid pressure and flow velocity were made in the carotid artery of 65 healthy normotensive individuals (age 21–78 yr; 43 male) and pulse wave analysis, wave intensity analysis and wave separation was performed; waveforms were classified into type A, B or C. AIx, the time of the first shoulder (Ts), wave reflection index (WRI) and the ratio of backward to forward pressure (Pb/Pf) were calculated.ResultsAIx did not correlate with log WRI or Pb/Pf. When AIx was restricted to positive values AIx and log WRI were positively correlated (r=0.33; p=0.04). In contrast log WRI and Pb/Pf were closely correlated (r=0.66; p<0.001). There was no correlation between the Ts and the timing of Pb or the reflected wave identified by wave intensity analysis. Wave intensity analysis showed that the morphology of type C waveforms (negative AIx) was principally due to a forward travelling (re-reflected) decompression wave in mid-systole. AIx correlated positively with age, inversely with height and was higher in women. In contrast log WRI and Pb/Pf showed negative associations with age, were unrelated to height and did not differ significantly by gender.ConclusionsAIx has serious limitations as a measure of wave reflection. Negative AIx values derived from Type C waves should not be used as estimates of wave reflection magnitude.